Helping women respond to the global food price crisis - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Bassett, Lucy; Usnick, Michael; Pandolfelli, Lauren; Morden, Cheryl; Alderman, Harold (International Food Policy Research Institute, 2008)
The current food price crisis has received widespread attention, but discussions to date have largely overlooked the gender dimensions of the crisis. More than 15 years of rigorous research on gender and intrahousehold resource allocation suggest not only that men and women will be affected differently by the global food crisis, but also that, as both consumers and producers, they will have different stocks of resources with which to respond to rising prices. Although the current situation calls for an urgent national and international response, urgency is not an excuse for misguided policies that fail to address the gender implications of the crisis. Instead, decisionmakers should take this opportunity to incorporate what is known about women's roles in agricultural production and household welfare, and the specific challenges they face, both to craft more effective policy responses and to enable women to respond better to the current challenges and opportunities.